Characterizing the mechanism of action of the Legionella pneumophila effector LegC4 - Brucken, Tshegofatso (My University, 2025)
Legionella pneumophila, a facultative intracellular bacterium, can cause Legionnaires’ disease in vulnerable populations by exploiting alveolar macrophages for replication. Among its arsenal of over 300 Dot/Icm-translocated effector proteins, LegC4 has emerged as a unique effector, playing a critical role in promoting bacterial fitness in protozoan hosts while paradoxically restricting bacterial replication in cytokine-activated macrophages and in the mouse lung. The focus of this dissertation was on characterizing the mechanisms of action of the effector LegC4 and its interactions with host processes and immune defenses, with the goal of uncovering novel innate immune strategies and identifying key targets of bacterial virulence factors. Previous studies established that LegC4 enhances cytokine-mediated restriction of L. pneumophila in macrophages and in vivo, highlighting its involvement in key immune pathways. Building on this foundation, I sought to investigate the mechanisms by which LegC4 contributes to host defense against L. pneumophila. We found that bacteria expressing legC4 are targeted to lysosomes in a cytokine-dependent manner. Additionally, our work identified host proteasome activator (PA) 28[alpha] as a key target of LegC4. The PA28[alpha][beta] complex facilitates the degradation of oxidant-damaged proteins during inflammation and oxidative stress. We found that in macrophages and mice lacking PA28[alpha][beta] (Psme1/2[superscript -/-]), LegC4-mediated restriction is abolished. Furthermore, we show that in the presence of LegC4, there is increased accumulation of oxidant-damaged proteins, and oxidative stress is sufficient to restrict bacterial replication. Given the targeting of legC4-expressing bacteria to lysosomes, we explored upstream mechanisms, focusing on the role of autophagy, a key cell-autonomous defense mechanism, in LegC4-mediated restriction. Our findings reveal that autophagy is essential for this process, as pharmacological inhibition of autophagy rescues bacterial replication of legC4-expressing bacteria. Moreover, we found that LegC4 enhances autophagy as shown by increased LC3 lipidation and autophagosome formation. Additionally, under oxidative stress conditions, LegC4 further enhances autophagic activity, emphasizing its role in promoting this crucial host defense strategy. In summary, this work provides novel insights into how LegC4 modulates bacterial fitness and effector-driven host immune responses to bolster host defenses. These findings contribute to the growing recognition of effector-triggered immunity as a component of innate defense mechanisms in metazoans. Notably, this study identifies a novel role for PA28[alpha][beta] in cell-autonomous immunity, demonstrating its contribution to host defenses against L. pneumophila. Overall, this research highlights the complex strategies employed by mammalian hosts to defend against intracellular pathogens and suggests new avenues for therapeutic interventions. Specifically, the potential of using bacterial effectors, like LegC4, as tools to enhance innate immune responses or modulate immune functions to target and inhibit intracellular pathogens.
Keywords: Legionella pneumophila; Effectors; LegC4; Proteasome activator (PA) 28αβ; Effector triggered immunity